Whole genome sequencing in the investigation of recurrent invasive Group A streptococcus outbreaks in a maternity unit - Dickinson, Harriet; Reacher, Mark; Nazareth, Bernadette; Eagle, Heidi; Fowler, Deirdre; Underwood, Anthony; Chand, Meera; Chalker, Victoria; Coelho, Juliana; Daniel, Roger; Kapatai, Georgia; Al-Shabib, Ali; et al. (Elsevier, 2018)
Background: The clinical manifestations of Group A streptococcus (GAS) – (Streptococcus pyogenes) are diverse, ranging from asymptomatic colonisation to devastating invasive disease. Maternity related clusters of invasive Group A streptococcus (iGAS) infection are complex to investigate and control, especially if recurrent.